Motivation for Women of Age Fertile to Attitude in Do Screening Cancer Cervix - Rieh Firdausi; Fitri Ayatul Azlina; Edita Pusparatri (Indonesian Journal of Global Health Research, 2026)
Cancer cervix is reason main deaths in women , especially in developing countries. Detection early through screening is very important For pressing number incidents and deaths , but participation woman age fertile (WUS) still low. Motivation become influencing factors attitude they to examination. Know connection between WUS motivation with attitude to screening cancer cervix. Method: Study descriptive quantitative with approach cross-sectional. Sample as many as 94 WUS were selected with Purposive sampling in Sungai Rangas Ulu Village. Data collected through questionnaire and analyzed using correlation test. The validity test on both questionnaires is said to be valid because it is > 0.361 (r table) and the reliability value is said to be reliable where the Cronbach's alpha value is > 0.6. Results: Average age respondents 34.70 years old, majority educated basic (54.30%), no working (52.10%), and earning low (87.20%). There is connection weak positive but significant between motivation and attitude to screening cancer cervix (r = 0.308, p = 0.003). Improvement motivation through education and access service can increase WUS participation in detection early cancer cervix.